The relationship between the presence of antibodies and direct detection of Toxoplasma gondii in slaughtered calves and cattle in four European countries - Opsteegh, M.; Spano, F.; Aubert, D.; Balea, A.; Burrells, A.; Cherchi, S.; Cornelissen, J.B.W.J.; Dam-Deisz, C.; Guitian, J.; Györke, A.; Innes, E.A.; Katzer, F.; et al. (International journal for parasitology, 2019)
[Display omitted] •Toxoplasma gondii parasites or DNA were detected in 13 out of 401 cattle.•Detection of viable T. gondii in 1.6% of cattle by mouse bioassay is reported.•There was no concordance between MAT or p30 immunoblot and direct detection of T. gondii.•MAT or p30 immunoblot results are no proxy for the presence of T. gondii in cattle. In cattle, antibodies to Toxoplasma gondii infection are frequently detected, but evidence for the presence of T. gondii tissue cysts in cattle is limited. To study the concordance between the presence of anti-T. gondii IgG and viable tissue cysts of T. gondii in cattle, serum, liver and diaphragm samples of 167 veal calves and 235 adult cattle were collected in Italy, the Netherlands, Romania and the United Kingdom. Serum samples were tested for anti-T. gondii IgG by the modified agglutination test and p30 immunoblot. Samples from liver were analyzed by mouse bioassay and PCR after trypsin digestion. In addition, all diaphragms of cattle that had tested T. gondii-positive (either in bioassay, by PCR on trypsin-digested liver or serologically by MAT) and a selection of diaphragms from cattle that had tested negative were analyzed by magnetic capture quantitative PCR (MC-PCR). Overall, 13 animals were considered positive by a direct detection method: seven out of 151 (4.6%) by MC-PCR and six out of 385 (1.6%) by bioassay, indicating the presence of viable parasites. As cattle that tested positive in the bioassay tested negative by MC-PCR and vice-versa, these results demonstrate a lack of concordance between the presence of viable parasites in liver and the detection of T. gondii DNA in diaphragm. In addition, the probability to detect T. gondii parasites or DNA in seropositive and seronegative cattle was comparable, demonstrating that serological testing by MAT or p30 immunoblot does not provide information about the presence of T. gondii parasites or DNA in cattle and therefore is not a reliable indicator of the risk for consumers.